Peptidomimetic bond formation by DNA-templated acyl transfer. - Mckee, M; Evans, A; Gerrard, SR; O'Reilly, R; Turberfield, A; Stulz, E (2011)
The efficiencies of DNA-templated acyl transfer reactions between a thioester modified oligonucleotide and a series of amine and thiol based nucleophiles are directly compared. The reactivity of the nucleophile, reaction conditions (solvent, buffer, pH) and linker length all play important roles in determining the efficiency of the transfer reaction. Careful optimisation of the system enables the use of DNA-templated synthesis to form stable peptide-like bonds under mild aqueous conditions close to neutral pH.